A Framework and Databases for Measuring Entrepreneurial Ecosystems - Johnson, Evan; Hemmatian, Iman; Lanahan, Lauren; Joshi, Amol M. (Research Policy, 2022)
Scholarly literature on the concept of entrepreneurial ecosystems has increased sharply over the past five years. The surge in interest has also heightened the demand for robust empirical measures that capture the complexity of dynamic relationships among ecosystem constituents. We offer a framework for measurement that places collaborative relationships among entrepreneurs, firms, government agencies, and research institutions at the center of the ecosystem concept. We further emphasize the four roles of the federal government as a catalyst, coordinator, certifier, and customer in shaping these relationships. Despite the central importance of these firm-government interactions, there is surprisingly little research on suitable methodologies and appropriate data for systematically and reliably incorporating them into measures of ecosystem health. Our study aims to address this gap in the literature by first developing a conceptual framework for measuring entrepreneurial ecosystems and then describing an array of accompanying databases that provide rich and detailed information on firms and their relationships with government organizations, accelerators, and research institutions. A major advantage of our approach is that all the underlying databases are drawn from non-confidential, publicly available sources that are transparently disclosed and regularly updated. This greatly expands the potential community of scholars, managers, and policymakers that may independently use these databases to test theories, make decisions, and formulate policies related to innovation and entrepreneurship.